2017
DOI: 10.1161/circresaha.116.309782
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Proteome Analysis Identifies the Complete Secretome as the Functional Unit of Human Cardiac Progenitor Cells

Abstract: Rationale Cardiac progenitor cells are an attractive cell type for tissue regeneration but their mechanism for myocardial remodeling is still unclear. Objective This investigation determines how chronological age influences the phenotypic characteristics and the secretome of human cardiac progenitor cells (CPCs), as well as their potential to recover injured myocardium. Methods and Results Adult (aCPCs) and neonatal (nCPCs) cells were derived from patients more than 40 years or less than one month of age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
187
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(199 citation statements)
references
References 87 publications
(81 reference statements)
8
187
1
3
Order By: Relevance
“…Consistent with this hypothesis, current report by Sharma et al 7 observed nCPCs transplantation post-MI was associated with greater cell retention and functional benefit compared to aCPCs. Furthermore, a recent report using c-kit BAC -EGFP mouse has shown substantial cardiac regeneration in the cryo-injured neonatal hearts, in-part via contribution of c-kit + CPC to cardiomyogenesis and angiogenesis 9 .…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Consistent with this hypothesis, current report by Sharma et al 7 observed nCPCs transplantation post-MI was associated with greater cell retention and functional benefit compared to aCPCs. Furthermore, a recent report using c-kit BAC -EGFP mouse has shown substantial cardiac regeneration in the cryo-injured neonatal hearts, in-part via contribution of c-kit + CPC to cardiomyogenesis and angiogenesis 9 .…”
supporting
confidence: 81%
“…However, as is the case with other adult progenitors, the regenerative potential of CPCs decline with advancement of age, and thus may not result in consistent and long lasting therapeutic effect 6 . On these lines, the current report in Circulation Research by Sharma et al 7 has shown that human neonatal CPCs (nCPCs) outperform human adult CPCs (aCPCs) in functional recovery post- myocardial infarction (MI), effects which are mediated at least in part by heat shock factor-1(HSF-1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…neovascularization, reduced apoptosis of endogenous cardiomyocytes, activation of tissue intrinsic progenitor cells or recruitment of cells beneficial for tissue repair [260,287,290]. Beside the donor´s health status, chronological age significantly influences the characteristics of the SC´s secretome and thereby affects their potential to promote myocardial recovery [291][292][293].…”
Section: Paracrine Signalingmentioning
confidence: 99%